TINJAUAN KONSEPTUAL MIKRO-MAKRO DAYA SAING DAN STRATEGI PEMBANGUNAN PERTANIAN (Forum Penelitian Agro Ekonomi, 2017)
Policy makers and economists are interested in competitiveness concept and try to implement in the economic development. Competitiveness has several perspectives, i.e. economic perspective, business, and politic. Competitivess could also be reviewed in a micro perspective (company level) and macro perspective (national level). This paper examines the competitiveness concept in terms of micro and macro perspectives. The micro perspective would be useful in agricultural development, especially in crop selection and in endeavor to change comparative to competitive advantages. The macro perspective should be useful to improve national competitiveness trough various fiscal policies of real sector. The study revealed that several agricultural commodities have competitive and comparative advantages, but the competitiveness susceptible to external fluctuation. The changes from comparative to competitive advantage require government intervention to control market distortion and to reduce the high transaction cost economy. Meanwhile, the changes from competitiveness at company level to competitiveness at national level need an integrated macro economic policies and micro economic activities.
Keywords: competitiveness; micro-macro; strategy; development; agriculture; daya saing; mikro-makro; strategi; pembangunan; pertanian